Hamilton Fish papers - Fish, Hamilton, 1808-1893.; Moore, John Bassett, 1860-1947.
Correspondence, journals, diaries, subject files, scrapbooks, printed matter, and other papers relating chiefly to Fish's service as U.S. secretary of state under Ulysses S. Grant and as U.S. representative and senator from and governor of New York. Includes material pertaining to his activities in the Society of the Cincinnati and to family and business affairs. Subjects include Alabama claims and the Geneva Arbitration Tribunal; the Treaty of Washington with Great Britain in 1871; Canadian reciprocity; fisheries; relations with Cuba, Haiti, Santo Domingo, and Spain; and the annexation of Texas. Also includes the John Bassett Moore file containing typewritten transcripts of Fish's correspondence, principally from the General Correspondence series, selected and prepared by Moore along with Moore's notes, memoranda, and related correspondence.
Correspondents include Charles Francis Adams, Amos Tappan Akerman, Henry B. Anthony, Chester Alan Arthur, J. Hubley Ashton, Orville Elias Babcock, Adam Badeau, George Bancroft, James M. Barrien, William W. Belknap, John Armor Bingham, James Gillespie Blaine, G.W. Blunt, George S. Boutwell, Benjamin Helm Bristow, Benjamin F. Butler, John L. Cadwalader, Simon Cameron, Zachariah Chandler, Salmon P. Chase, Robert S. Chew, George William Childs, Roscoe Conkling, John A.J. Creswell, Wm. Henry Crosby, Andrew Gregg Curtin, Caleb Cushing, J.C. Bancroft Davis, Columbus Delano, Thomas B. Dibblee, John A. Dix, George F. Edmunds, William Maxwell Evarts, Millard Fillmore, Frederick T. Frelinghuysen, Asa Bird Gardiner, James A. Garfield, Ulysses S. Grant, Horace Greeley, Moses Hicks Grinnell, Alexander Hamilton, Jr., Rutherford Birchard Hayes, E.R. Hoar, Washington Hunt, John Jay, Marshall Jewell, Francis Lieber, William L. Marcy, Matthew Fontaine Maury, Benjamin Moran, Edwin D. Morgan, Robert Hunter Morris, Oliver P. Morton, John Lothrop Motley, Edwards Pierrepont, John M. Read, William A. Richardson, George M. Robeson, Robert Cumming Schenck, John Schuyler, Winfield Scott, William Henry Seward, John Sherman, Daniel Edgar Sickles, Charles Sumner, Zachary Taylor, J.R. Van Rensselaer, E.B. Washburne, Thurlow Weed, George H. Williams, and Robert C. Winthrop.
Microfilm edition of diaries, 1869-1876, (containers 277-287) available
Microfilm edition of governor's papers, 1836-1850, (containers 256-275) available
Microfilm produced from originals in the Manuscript Division.
U.S. secretary of state and U.S. senator and representative from and governor of New York.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Adams, Charles Francis, -- 1807-1886 -- Correspondence; Akerman, Amos Tappan, -- 1821-1880 -- Correspondence; Anthony, Henry B. -- 1815-1884 -- Correspondence; Arthur, Chester Alan, -- 1829-1886 -- Correspondence; Ashton, J. Hubley -- 1836-1907 -- Correspondence; Babcock, Orville Elias, -- 1835-1884 -- Correspondence; Badeau, Adam, -- 1831-1895 -- Correspondence; Bancroft, George, -- 1800-1891 -- Correspondence; Barrien, James M. -- Correspondence; Belknap, William W. -- 1829-1890 -- Correspondence; Bingham, John Armor, -- 1815-1900 -- Correspondence; Blaine, James Gillespie, -- 1830-1893 -- Correspondence; Blunt, G. W. -- 1802-1878 -- Correspondence; Boutwell, George S. -- 1818-1905 -- Correspondence; Bristow, Benjamin Helm, -- 1832-1896 -- Correspondence; Butler, Benjamin F. -- 1795-1858 -- Correspondence; Cadwalader, John L. -- 1836-1914 -- Correspondence; Cameron, Simon, -- 1799-1889 -- Correspondence; Chandler, Zachariah, -- 1813-1879 -- Correspondence; Chase, Salmon P. -- 1808-1873 -- Correspondence; Chew, Robert S. -- Correspondence; Childs, George William, -- 1829-1894 -- Correspondence; Conkling, Roscoe, -- 1829-1888 -- Correspondence; Creswell, John A. J. -- 1828-1891 -- Correspondence; Crosby, Wm. Henry -- 1808-1892 -- Correspondence; Curtin, Andrew Gregg, -- 1815-1894 -- Correspondence; Cushing, Caleb, -- 1800-1879 -- Correspondence; Davis, J. C. Bancroft -- 1822-1907 -- Correspondence; Delano, Columbus, -- 1809-1896 -- Correspondence; Dibblee, Thomas B. -- Correspondence; Dix, John A. -- 1798-1879 -- Correspondence; Edmunds, George F. -- 1828-1919 -- Correspondence; Evarts, William Maxwell, -- 1818-1901 -- Correspondence; Fillmore, Millard, -- 1800-1874 -- Correspondence; Frelinghuysen, Frederick T. -- 1817-1885 -- Correspondence; Gardiner, Asa Bird, -- 1839-1919 -- Correspondence; Garfield, James A. -- 1831-1881 -- Correspondence; Grant, Ulysses S. -- 1822-1885.; Grant, Ulysses S. -- 1822-1885 -- Correspondence; Greeley, Horace, -- 1811-1872 -- Correspondence; Grinnell, Moses Hicks, -- 1803-1877 -- Correspondence; Hamilton, Alexander, -- 1786-1875 -- Correspondence; Hayes, Rutherford Birchard, -- 1822-1893 -- Correspondence; Hoar, E. R. -- 1816-1895 -- Correspondence; Hunt, Washington, -- 1811-1867 -- Correspondence; Jay, John, -- 1817-1894 -- Correspondence; Jewell, Marshall, -- 1825-1883 -- Correspondence; Lieber, Francis, -- 1800-1872 -- Correspondence; Marcy, William L. -- 1786-1857 -- Correspondence; Maury, Matthew Fontaine, -- 1806-1873 -- Correspondence; Moran, Benjamin, -- 1820-1886 -- Correspondence; Morgan, Edwin D. -- 1811-1883 -- Correspondence; Morris, Robert Hunter, -- 1802-1855 -- Correspondence; Morton, Oliver P. -- 1823-1877 -- Correspondence; Motley, John Lothrop, -- 1814-1877 -- Correspondence; Pierrepont, Edwards, -- 1817-1892 -- Correspondence; Read, John M. -- 1797-1874 -- Correspondence; Richardson, William A. -- 1821-1896 -- Correspondence; Robeson, George M. -- 1829-1897 -- Correspondence; Schenck, Robert Cumming, -- 1809-1890 -- Correspondence